Anti-SARS CoV-2 IgG in COVID-19 Patients with Hematological Diseases: A Single-center, Retrospective Study in Japan - Fujii, Takayuki; Hagihara, Masao; Mitamura, Keiko; Nakashima, Shiori; Ohara, Shin; Uchida, Tomoyuki; Inoue, Morihiro; Okuda, Moe; Yasuhara, Atsuhiro; Murakami, Jurika; Duong, Calvin; Iwatsuki-Horimoto, Kiyoko; et al. (Internal Medicine, 2022)
Objective Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread globally. Although the relationship between anti-SARS-CoV-2 immunoglobulin G (IgG) antibodies and COVID-19 severity has been reported, information is lacking regarding the seropositivity of patients with particular types of diseases, including hematological diseases. Methods In this single-center, retrospective study, we compared SARS-CoV-2 IgG positivity between patients with hematological diseases and those with non-hematological diseases. Results In total, 77 adult COVID-19 patients were enrolled. Of these, 30 had hematological disorders, and 47 had non-hematological disorders. The IgG antibody against the receptor-binding domain of the spike protein was detected less frequently in patients with hematological diseases (60.0%) than in those with non-hematological diseases (91.5%; p=0.029). Rituximab use was significantly associated with seronegativity (p=0.010). Conclusion Patients with hematological diseases are less likely to develop anti-SARS-CoV-2 antibodies than those with non-hematological diseases, which may explain the poor outcomes of COVID-19 patients in this high-risk group.